Current Topics on Superfoods - Shiomi, Naofumi (IntechOpen, 2018)
Superfood is a food that contains active ingredients or important nutrients at extremely high levels. Protective effects of superfoods on diseases have been remarked. Recently, several foods such as camu camu, chia seeds and goji berries are well known, and their trade has been rapidly increasing in the past 10 years. The purpose of this book is the development of a novel concept of superfoods and diet-containing superfoods. In the chapters, researchers have introduced the active components of superfoods and diets using such foods. Superfoods derived from fish and by-products of beer brewing are also introduced. Moreover, the procedure of bio-accessibility is also considered. I expect that the readers understand this novel concept of superfoods.